2007
DOI: 10.1002/14651858.cd005040.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone for autism spectrum disorder

Abstract: BackgroundAutistic spectrum disorder encompasses a wide variety of behavioural and communicative problems. Both the core features and noncore features of autism have been targeted in a variety of therapies. Atypical antipsychotic medications, including risperidone, have been used for symptom and behaviour improvement and have shown beneficial outcomes, particularly in certain aspects of the disorder. However, given the nature of the condition presenting in young patients, the risks of these potentially long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 56 publications
2
36
0
2
Order By: Relevance
“…29 Since 2006, the US Food and Drug Administration has approved 2 atypical antipsychotic medications for treatment of irritability in autistic disorder (risperidone for children 5 to 16 years and aripiprazole for those aged 6 to 17 years), and the a-agonists guanfacine and clonidine have been approved for treatment of ADHD in new extended release formulations for children aged 6 to 17 years. The evidence for effectiveness of medications is gradually accumulating, 30,31 and physician prescription of these medicines to treat ASD and comorbid psychiatric conditions will likely increase with time.…”
Section: Studies Conducted By the Researchmentioning
confidence: 99%
“…29 Since 2006, the US Food and Drug Administration has approved 2 atypical antipsychotic medications for treatment of irritability in autistic disorder (risperidone for children 5 to 16 years and aripiprazole for those aged 6 to 17 years), and the a-agonists guanfacine and clonidine have been approved for treatment of ADHD in new extended release formulations for children aged 6 to 17 years. The evidence for effectiveness of medications is gradually accumulating, 30,31 and physician prescription of these medicines to treat ASD and comorbid psychiatric conditions will likely increase with time.…”
Section: Studies Conducted By the Researchmentioning
confidence: 99%
“…Several open trials of risperidone in autism (reviewed in 3,4 ) and three placebo double-blind randomized controlled trials, [5][6][7] reported significant improvements in at least half of the patients evaluated. 4,8 Risperidone was shown to be well tolerated and effective in treating aggressiveness, hyperactivity, irritability, self-injurious behaviours, stereotipies, social withdrawal and lack of interest. According to one study, sensorimotor functioning and affectual relations (abrupt changes in affect, crying, temper outbursts) are also improved.…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, sensorimotor functioning and affectual relations (abrupt changes in affect, crying, temper outbursts) are also improved. 6,8 Though risperidone significantly improves behavioural problems in most situations, it is also associated with mild adverse effects. The most common adverse drug reactions (ADR) while taking risperidone are sedation/drowsiness, weight gain, hyperprolactinemia and extrapyramidal symptoms, especially tardive dyskinesias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we included 17 systematic reviews. 4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Results from systematic reviews A summary of each systematic review is presented narratively below. In addition, Table 2 4,10-25 presents the issues addressed, the main findings from each systematic review and the quality of the evidence (based on the GRADE approach).…”
Section: Search Resultsmentioning
confidence: 99%